Sturge-Weber syndrome in childhood lupus complicated by macrophage activation syndrome - Manisha Jethwa; Vishalakshi Viswanath; Mayuri Dhakne; Pradnya R Joshi (Wolters Kluwer Medknow Publications, 2023)
Sturge-Weber syndrome (SWS) is an uncommon, nonhereditary developmental condition characterized by nevus flammeus and ocular and neurological manifestations. Childhood-onset systemic lupus erythematosus (cSLE) is a rare disease with a female preponderance and is associated with multiple complications and a poor prognosis. The coexistence of cSLE and SWS is uncommon and can be associated with an increased risk of thromboembolic and neuropsychiatric complications. Macrophage activation syndrome (MAS) is one of the fatal complications of cSLE and an early diagnosis based on clinical findings and laboratory parameters is vital. We report a rare and unique case of SWS with cSLE in an 11-year-old boy, which was complicated by MAS.